Буудайн ургах орчин - Д, Аззаяа; Э, Эрдэнэбат (Scientific transaction of the National University of Mongolia. Physics, 2022)
In this article we tried to study the difference between air and land surface temperature in the ordinary condition and in the vegetation cover. The purpose of this article is find the value of the difference and the impact of the vegetation cover to temperature. During this study we have got some results, for example air and land surface temperature are changed according the vegetation cover. The difference of these temperatures is 1.7-17.8oC.